STRATIGRAPHY AND COMPOSITION OF LAVA FLOWS IN MARE NUBIUM AND MARE COGNITUM - Bugiolacchi R.; Guest J.E.; Spudis P.D. (My University, 2006)
Three major periods of basaltic activity characterize the infill of the basins. Each of these periods was itself punctuated by discrete phases of widespread magma eruptions: three during both the Late Imbrian Epoch and the early Eratosthenian Period and then two in the late Eratosthenian Period. We found the youngest lavas off the eastern border of the Fra Mauro peninsula and, mantling a much larger area, over most of the central western Nubium basin. Our results place the Nubium/Cognitum basalts in the low-Ti category (1-5 wt% TiO2). The data indicate that the majority (~90%) of the mare terrain has iron content between 18 and 22 wt%. In particular, FeO contents tend to concentrate toward two compositional poles, each of ~20 wt%, and a much smaller one of ~15 wt%. These values are typical of nearside lunar maria. To complement our compositional data, we present a census of craters larger than 500 m using Orbiter IV images. The result was a crater count average with frequency 5.6 × 10-2 km-2, translating into an inferred mean age of 3300 Ma for the exposed lava flows. By combining lava chemistry with age, we find a possible correlation between the ages of the most prominent flow units and their estimated titanium content, with younger basalts becoming progressively Ti-richer with time (from 2-3 to 4-5 wt% TiO2). © The Meteoritical Society, 2006.